Adoption of a Digital Patient Health Passport as Part of a Primary Healthcare Service Delivery: Systematic Review - Tuan Yuswana Tuan Soh; Nik Mohd Mazuan Nik Mohd Rosdy; Mohd Yusmiaidil Putera Mohd Yusof; Syathirah Hanim Azhar Hilmy; Budi Aslinie Md Sabri (MDPI, 2024)
Indexed by Scopus